2003
DOI: 10.1023/b:jarg.0000013650.76052.ae
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Interleukin-1 and the Interleukin-1 Receptor Antagonist in In Vitro Embryo Development Among Women Undergoing In Vitro Fertilization–Embryo Transfer

Abstract: Purpose : To examine the roles of Interleukin-1 (IL-1) and IL-1 receptor antagonist (IL-1ra), in in vitro embryo development and subsequent pregnancy outcome. Methods : Maternal serum utilized to supplement embryo growth in IVF cycles was analyzed for the presence of IL-1 cytokines. Results : The maternal serum that was utilized to supplement the embryo media was found to have measurable amounts of IL-1β and IL-1ra. Conclusions : Relative antagonism of the IL-1 system was positively associated with embryo deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…Presently, there is accumulating evidence suggesting that individual cytokines in human follicular fluid can be used as predictors of IVF outcome [30]. A positive association of IL-6 with oocyte maturation [31] and IL-1β with embryo development and pregnancy [32] is documented. A majority of findings have indicated that IL-12 is negatively associated with folliculogenesis, oocyte quality, and implantation [30,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there is accumulating evidence suggesting that individual cytokines in human follicular fluid can be used as predictors of IVF outcome [30]. A positive association of IL-6 with oocyte maturation [31] and IL-1β with embryo development and pregnancy [32] is documented. A majority of findings have indicated that IL-12 is negatively associated with folliculogenesis, oocyte quality, and implantation [30,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression level of IL-1β in the fallopian tubes was found to be higher in the stimulated groups than in the unstimulated control group. Several studies have indicated that higher levels of IL-1β negatively affect the fertilization process (14-16), embryonic implantation, and pregnancy outcomes (18)(19)(20), and can cause several different complications during pregnancy (21) and can be employed as a marker for tubal pregnancy (22). The elevated inflammatory response observed within the fallopian tube due to higher IL-1β levels, accompanied by the disturbed histoarchitecture of the fallopian tube, might directly affect the fertilization process.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines play an important role in implantation and early pregnancy [ 16 , 28 ] . For example, IL-1 receptors have been shown to be located on the early human embryo, emphasizing the important role of IL1-ra in early pregnancy [ 18 ]. Therefore, we aimed to establish chemokines as biomarkers at the time of pregnancy testing, some of which were found to be changed in patients with proven abortions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower levels of interleukin 1-receptor antagonist (IL-1ra) prior to embryo transfer were associated with lower pregnancy rates [ 18 ] . Higher levels of Thyreoperoxidase (TPO) and lower concentrations of Granulocyte-Colony Stimulating Factor (GCSF) were significantly associated with the risk of spontaneous abortion in women prior to report of miscarriage.…”
Section: Introductionmentioning
confidence: 99%